Ergonomic risk identification of left-handed clinicians using right hand-designed extraction forceps in simple extraction cases of the UPCD Student from Batch 2011 to 2013 - Belen, Precien Anne S.; Redecio, Ruby Jean S.C.; Rosanes, Rose Anne Q. (Adviser).
Extraction forceps which are designed to be used by the right hand present a challenge for the left-handed clinicians. Even minor pain and discomfort, it felt repetitively, poses a risk for musculosketetal injuries and may hinder a clinician's ability to perform the task efficiently and safety. This study attempted to determine the efficiency and safety in performing simple extraction, and the presence of pain or discomfort in using right hand-designed forceps by left-handed clinicians through a modified ergonomic assessment tool. Methods: Identified seventeen left-handed clinicians from the University of the Philippines Manila College of Dentistry were gathered through total enumeration. Modified Ergonomic Risk Identification tool based on NIOSH standard had undergone pilot testing before it was answered by the left-handed clinicians. Informed consent was also obtained. Frequency and percentage were computed for qualitative variables. Microsoft Excel 2010 was used to encode the data and to produce the tables and graphs. Results: Fifteen (15) out of the 17 left-handed participants reported that they can finish an extraction procedure within 20 minutes, a duration deemed acceptable. The use of forceps based on the characteristics on materials handling such as easy to grasp, stable, able to be held without slipping, and designed that it does not dig into the palm, my be regarded as safe. However, the characteristic that is designed to be used by either hand suggests that it is not safe. Lastly, 65% have reported pain or discomfort upon using forceps and thirty-five percent (35%) experienced none. Conclusion: The use of right hand-designed forceps caused pain discomfort to majority of the left-handed clinicians of the UPCD from Batch 2011 to 2013, though they can still perform extraction efficiently and safely regardless of the forceps used.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.